The Dual Path to Brand Attitude: Perceived Brand Globalness and Localness in McDonald’s Indonesia and the Mediating Role of Brand Authenticity - Ann Maritza Wattimena; Charly Hongdiyanto (Dinasti Review, 2026)
Global brands operating in emerging markets often face the challenge of balancing global identity with local adaptation. This study aims to examine the influence of perceived brand globalness, perceived brand localness, and brand authenticity on brand attitude among consumers of McDonalds in Java. The research uses a quantitative method through a questionnaire distributed to respondents in East Java, Central Java, and West Java. The results show that perceived brand globalness and perceived brand localness do not directly influence brand attitude. However, both variables significantly increase brand authenticity. Brand authenticity becomes the strongest factor shaping brand attitude and serves as the connecting mechanism through which globalness and localness affect consumer evaluations. These findings indicate that global image and local adaptation are effective only when they build a brand perception that feels honest, consistent, and trustworthy. Overall, this study highlights the importance of authenticity in shaping positive brand attitudes toward global brands in Java, Indonesia.